THE ROLE OF THE HORMONAL BACKGROUND OF THE ORGANISM ON GROWTH AND DEVELOPMENT OF ORAL CAVITY TISSUES - Gafforov, S.A.; Akhmadaliyev, N.N.; Akhmedov, A.B. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Pathologies of the maxillofacial area is one of the most common types of pathology in dentistry and has a widespread prevalence regardless of gender and age. Violations in the dental system lead to a number of negative consequences, accompanied by changes in the functioning of many body systems. The review is devoted to the analysis of hormonal factors, identifying the mechanisms of their occurrence in violation of the body’s hormonal background. The information presented in the article broadens the understanding of the causes of various pathologies of hard dental tissues.